2011
DOI: 10.1007/s10482-011-9666-y
|View full text |Cite
|
Sign up to set email alerts
|

Survival and biofilm formation by Group B streptococci in simulated vaginal fluid at different pHs

Abstract: The Group B Streptococcus (GBS, Streptococcus agalactiae) is an important cause of neonatal and maternal infection. GBS is a commensal organism of the lower gastrointestinal and vaginal tract. A frequent mode of neonatal infection is vertical transmission from pregnant women to their foetus or neonate. The aim of this study was to evaluate the survival and biofilm production of 10 GBS strains in simulated vaginal fluid at pH 4.2, 5.5 and 6.5. GBS survived longer at higher pH than at normal vaginal pH. At pH 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 17 publications
1
49
0
1
Order By: Relevance
“…In a recent study, Ho et al (37) found that a low pH induced biofilm formation in nutrientlimited medium (M9YE) but not in THB. Borges et al (27), Kaur et al (28), and Yang et al (38) found that GBS produced a greater amount of biofilm at pH 6.5 than at pH 4.2, and Konto-Ghiorghi et al (29) reported that a uniform biofilm was produced only on LB and RPMI 1640 supplemented with 1% glucose and not on THB. Manetti et al (39) observed that in S. pyogenes, the presence of glucose resulted in autoacidification of the medium and consequently biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent study, Ho et al (37) found that a low pH induced biofilm formation in nutrientlimited medium (M9YE) but not in THB. Borges et al (27), Kaur et al (28), and Yang et al (38) found that GBS produced a greater amount of biofilm at pH 6.5 than at pH 4.2, and Konto-Ghiorghi et al (29) reported that a uniform biofilm was produced only on LB and RPMI 1640 supplemented with 1% glucose and not on THB. Manetti et al (39) observed that in S. pyogenes, the presence of glucose resulted in autoacidification of the medium and consequently biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated GBS biofilm formation in vitro (26)(27)(28)(29), although the data regarding the effects of pH and medium composition are controversial. In a recent study, Ho et al (37) found that a low pH induced biofilm formation in nutrientlimited medium (M9YE) but not in THB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the GBS CovR/S system responds to pH wherein increased CovR/S regulation was observed under low (acidic) pH [65, 7173]. Changes in pH also influences GBS adhesion [72, 74], survival [75], and biofilm formation [76, 77]. Of note, high vaginal pH and a non-lactobacilli dominated vaginal microbiome [78] are associated with women of African descent with higher incidence of GBS vaginal colonization [15, 21, 22] and neonatal disease [2325].…”
Section: Bacterial Factors That Promote Gbs Vaginal Colonization Ascmentioning
confidence: 99%